2005
DOI: 10.1103/physreve.72.031808
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of poly(ethylene oxide) in a blend with poly(methyl methacrylate): A quasielastic neutron scattering and molecular dynamics simulations study

Abstract: In this paper, we have addressed the question of the dynamic miscibility in a blend characterized by very different glass-transition temperatures, Tg, for the components: poly(ethylene oxide) and poly(methyl methacrylate) (PEO/PMMA). The combination of quasielastic neutron scattering with isotopic labeling and fully atomistic molecular dynamics simulations has allowed us to selectively investigate the dynamics of the two components in the picosecond-10 nanoseconds scale at temperatures close and above the Tg o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
180
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(215 citation statements)
references
References 63 publications
35
180
0
Order By: Relevance
“…Samples. Two PMMA samples (Polymer Source, Inc.) with different deuteration levels were investigated: fully deuterated (PMMA-d 8 ) and a protonated material including deuterated ester methyl groups (PMMA-d 3 ). The molecular weights and polydispersities were M w ) 26 800 and 25 300 g/mol and M w /M n ) 1.04 and 1.09, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Samples. Two PMMA samples (Polymer Source, Inc.) with different deuteration levels were investigated: fully deuterated (PMMA-d 8 ) and a protonated material including deuterated ester methyl groups (PMMA-d 3 ). The molecular weights and polydispersities were M w ) 26 800 and 25 300 g/mol and M w /M n ) 1.04 and 1.09, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The homopolymer investigated as reference showed extremely strong deviations from the Gaussian approximation for the average self-correlation function of all PMMA hydrogens that were experimentally accessed. The second work 8 did not report on the homopolymer dynamics. Finally, in the neutron spin-echo study on collective motion, 20 the temperature range was restricted to only two temperatures very close to T g for pure PMMA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We note that it has been reported that QENS data for this system indicate confinement below the T g of PMMA, where the system may be regarded as mobile PEO segments "confined" by the immobile PMMA. 12 It may be that the character of the observed process changes under these conditions (PEO confined between immobile PMMA segments) and is no longer represented by models designed to describe the R-relaxation. The R-relaxation of PEO has been reported to disappear entirely when confined in other systems, which is consistent with all the above evidence.…”
Section: Comparison To Dynamic Modelsmentioning
confidence: 99%
“…1,2 The difference in glass transition temperatures [T g 's] between PEO and PMMA is significant (∼180 K), with PEO having the low T g and thus being the more mobile component. Two dynamic responses are observed through a variety of experimental techniques, [3][4][5][6][7][8][9][10][11][12] and two glass transitions have recently been reported. 58 If characteristic relaxation times are compared at a common temperature, the mobility of PMMA increases with blending while that of PEO decreases.…”
Section: Introductionmentioning
confidence: 99%